Osteoarthritis of the hip and occupational lifting. - Coggon, D; Kellingray, S; Inskip, H; Croft, P; Campbell, L; Cooper, C (1998)
To test the hypothesis that occupational lifting is a cause of hip osteoarthritis, the authors examined associations with lifting and other occupational activities in a case-control study. The study was performed in two English health districts (Portsmouth and North Staffordshire) from 1993 to 1995. A total of 611 patients (210 men and 401 women) listed for hip replacement because of osteoarthritis over an 18-month period were compared with an equal number of controls selected from the general population and individually matched for age, sex, and general practice. Information about suspected risk factors was obtained by a questionnaire administered at interview and a short physical examination. Analysis was by conditional logistic regression. After adjustment for potential confounders, the risk in men increased progressively with the duration and heaviness of occupational lifting. Relative to those with low exposure, men who had regularly lifted weights in excess of 50 kg for 10 years or longer had an odds ratio of 3.2 (95% confidence interval 1.6-6.5). No comparable association was found in women. Of the other occupational activities examined, only frequent climbing of stairs showed a pattern suggestive of a causal relation. These findings are consistent with the results of other studies, and there is now a strong case for regarding hip osteoarthritis as an occupational disease in men whose work has involved prolonged and frequent heavy lifting.